Weight Status and Attentional Biases Toward Foods: Impact of Implicit Olfactory Priming - Mas, Marine; Brindisi, Marie-Claude; Chabanet, Claire; Nicklaus, Sophie; Chambaron, Stéphanie (Frontiers in Psychology, 2019)
Objective: Numerous studies highlight the involvement of cognitive factors in the development and maintenance of obesity. We aimed to measure attentional biases (AB) toward foods (i.e., the individual tendency to automatically orient one’s attention toward food stimuli) in normal-weight (NW) individuals and those with overweight (OW) and obesity (OB). We evaluated whether implicit or explicit exposure to olfactory food cues could modify AB. Methods: Eighty-five participants with different weight statuses took part in this experiment. We measured AB toward food pictures with an adapted visual probe task and the variations in AB, while participants were primed with olfactory food cues (within-subject design: no odor/low-energy dense food odor/high-energy dense food odor). Odors were non-attentively perceived during session 1 (implicit condition) and attentively perceived during session 2 (explicit condition). Results: Our results highlighted AB toward food pictures, especially when foods were energy dense, regardless of weight status (p < 0.001). The olfactory priming effect was only significant in the implicit condition. Participants with obesity had a stronger AB toward foods when they were primed with a non-attentively perceived high-energy dense food odor than with a non-attentively perceived low-energy dense food odor (p = 0.02). The trend was reversed for normal-weight participants, while no significant effect was found for participants with overweight. Conclusion: Our results support the hypothesis that an obesity-specific cognitive vulnerability may influence the processing of food-related stimuli and only while food cues are non-attentively perceived. Future research should seek to understand the mechanisms of this phenomenon.